Influência dos procedimentos e modos de transferência no processo MAG na redução de deformações em painéis de estruturas navais - CABRAL, Tarcio dos Santos (Associação Brasileira de Soldagem, 2018)
The Growth in the Brazilian shipbuilding industry brought on numerous problems in the production line. Some of these problems are related to the manufacturing process, welding process, due to residual stress and distortions. In the present paper, the influence of the welding procedure (sequence and direction of welding and the use of back weld) was studied. Different welding processes with different transfer modes (GMAW-CC, GMAW-TT and GMAW-CW) were also used. These changes were made to observe the influences on the amplitude of the distortions. All the welds were made using the ER70S-6 electrode and pure CO2 as a shielding gas with the short circuit transfer mode. The results showed that the most important variable is the direction of welding, which is related to the level of restriction of the panels welded. The effect of the welding sequence presented on the values of distortion produced were minor. The panels produced using the back welding procedure presented small values of distortion however, the procedure showed to be inefficient. It was also observed that the level of distortion for the processes GMAW-CC and GMAW-STT showed similar values. On the other hand the values of distortion in the panel welded using the GMAW-CW process presented the lowest values.